c-Jun Overexpression Accelerates Wound Healing in Diabetic Rats by Human Umbilical Cord-Derived Mesenchymal Stem Cells - Chun Yue; Zi Guo; Yufang Luo; Jingjing Yuan; Xinxing Wan; Zhaohui Mo (Stem Cells International)
Objective. Mesenchymal stem cells (MSCs) are considered a promising therapy for wound healing. Here, we explored the role of c-Jun in diabetic wound healing using human umbilical cord-derived MSCs (hUC-MSCs). Methods. Freshly isolated hUC-MSCs were subjected to extensive in vitro subcultivation. The cell proliferative and migratory capacities were assessed by the Cell Counting Kit-8 and scratch assays, respectively. c-Jun expression was evaluated by RT-PCR and western blot analysis. The function of c-Jun was investigated with lentivirus transduction-based gene silencing and overexpression. Diabetes mellitus was induced in SD rats on a high-glucose/fat diet by streptozocin administration. Wounds were created on the dorsal skin. The effects of c-Jun silencing and overexpression on wound closure by hUC-MSCs were examined. Reepithelialization and angiogenesis were assessed by histological and immunohistochemical analysis, respectively. Platelet-derived growth factor A (PDGFA), hepatocyte growth factor (HGF), and vascular endothelial growth factor (VEGF) levels were determined by western blot analysis. Results. hUC-MSCs showed gradually decreased cell proliferation, migration, and c-Jun expression during subcultivation. c-Jun silencing inhibited cell proliferation and migration, while c-Jun overexpression enhanced proliferation but not migration. Compared with untransduced hUC-MSCs, local subcutaneous injection of c-Jun-overexpressing hUC-MSCs accelerated wound closure, enhanced angiogenesis and reepithelialization at the wound bed, and increased PDGFA and HGF levels in wound tissues. Conclusion. c-Jun overexpression promoted hUC-MSC proliferation and migration in vitro and accelerated diabetic wound closure, reepithelization, and angiogenesis by hUC-MSCs in vivo. These beneficial effects of c-Jun overexpression in diabetic wound healing by hUC-MSCs were at least partially mediated by increased PDGFA and HGF levels in wound tissues.